Cell-Type-Specific ROS–AKT/mTOR–Autophagy Interplay—Should It Be Addressed in Periimplantitis? - Mihai Butucescu; Marina Imre; Florentina Rus-Hrincu; Bianca Voicu-Balasea; Alexandra Popa; Mihai Moisa; Alexandra Ripszky; Cristina Neculau; Silviu Mirel Pituru; Simona Pârvu (Diagnostics)
Periimplantitis represents an inflammatory disease of the soft and hard tissues surrounding the osseointegrated dental implant, triggering progressive damage to the alveolar bone. Cumulative data have revealed that periimplantitis plays a crucial part in implant failure. Due to the strategic roles of autophagy and its upstream coordinator, the AKT/mTOR pathway, in inflammatory responses, the crosstalk between them in the context of periimplantitis should become a key research target, as it opens up an area of interesting data with clinical significance. Therefore, in this article, we aimed to briefly review the existing data concerning the complex roles played by ROS in the interplay between the AKT/mTOR signaling pathway and autophagy in periimplantitis, in each of the main cell types involved in periimplantitis pathogenesis and evolution. Knowing how to modulate specifically the autophagic machinery in each of the cellular types involved in the healing and osseointegration steps post implant surgery can help the clinician to make the most appropriate post-surgery decisions. These decisions might be crucial in order to prevent the occurrence of periimplantitis and ensure the proper conditions for effective osseointegration, depending on patients’ clinical particularities.